Higher Education and the American Dream : Success and Its Discontents - Lazerson, Marvin (Book collections on Project MUSE., 2010)
The book delivers a penetrating, nuanced account of American universities in the twenty-first century. Tackles topics that range from the rise of the managerial class to the failed attempts to reform practice in the classroom.